ANALISIS POSTUR KERJA DAN USULAN FASILITAS KERJA PADA PROSES PENDISTRIBUSIAN CYLINDER DENGAN MENGGUNAKAN METODE WERA dan NERPA DI PT. INDOGRAVURE - Efendi, Ilham; Nurhidayat, Asep Endih; Putra, Muhammad Fidiandri (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
PT. Indogravure is a company engaged in printing flexible packaging for the pharmaceutical, agro-farming, food and beverage industry segments. In the production process activities there are problems in the cylinder warehouse division, there are 4 (four) work processes that have a potential risk of injury, namely the cylinder taking process, the cylinder checking process, the cylinder transport process, and the cylinder distribution process in the form of musculoskeletal complaints experienced by workers. To identify these complaints, the Workplace Ergonomic Risk Assessment (WERA) and Novel Ergonomic Postural Risk Assessment (NERPA) methods are used. The aim is to determine the level of risk experienced by workers during the work process and provide suggestions for improvements that minimize the occurrence of MSDs complaints. From the research conducted, it was found that there are 3 work processes that have the highest risk, namely the first is the process of taking cylinders with a score of 31 (medium) based on the WERA method and the level of risk level is 7 (high) based on the NERPA method, the second is the process of transporting cylinders with a score 29 (medium) based on the WERA method and a risk level level of 7 (high) based on the NERPA method, the three cylinder distribution processes with a score of 39 (medium) based on the WERA method and a risk level level of 7 (high) based on the NERPA method. The proposals given in this study are assistive devices designed using CATIA V5R21 software in the form of hydraulic trolleys, ladder conveyors, and electric trolleys. Where in improving worker posture using the proposed assistive devices, evaluation results are obtained using CATIA V5R21 software with a (low) level of risk, then a re-analysis of the evaluation results is carried out using the software, there is a decrease in the level of risk using the WERA method in the process of taking cylinders from scores 31 (medium) becomes a score of 23 (low) and based on the NERPA method the risk level is 7 (high) to 3 (medium), in the process of transporting the cylinder from a score of 29 (medium) to a score of 21 (low) and based on the NERPA method the risk level is 7 ( high) to 3 (medium), and in the cylinder distribution process from a score of 39 (medium) to a score of 27 (low) and based on the NERPA method the risk level is 7 (high) to 3 (medium). With the proposed tool design, it is hoped that the work process can be carried out effectively, efficiently and in accordance with ergonomic values so that the level of risk of injury experienced by workers is reduced.